Measurement of the top quark mass using proton-proton data at (s)=7 and 8 TeV MEASUREMENT of the TOP QUARK MASS USING ⋯ V. KHACHATRYAN et al. - Khachatryan, V. (2016)
A new set of measurements of the top quark mass are presented, based on the proton-proton data recorded by the CMS experiment at the LHC at s=8 TeV corresponding to a luminosity of 19.7 fb-1. The top quark mass is measured using the lepton+jets, all-jets and dilepton decay channels, giving values of 172.35±0.16(stat)±0.48(syst) GeV, 172.32±0.25(stat)±0.59(syst) GeV, and 172.82±0.19(stat)±1.22(syst) GeV, respectively. When combined with the published CMS results at s=7 TeV, they provide a top quark mass measurement of 172.44±0.13(stat)±0.47(syst) GeV. The top quark mass is also studied as a function of the event kinematical properties in the lepton+jets decay channel. No indications of a kinematic bias are observed and the collision data are consistent with a range of predictions from current theoretical models of ttproduction.